What is the next chapter in the organized food retail industry in Portugal, up to 2030, and what are the strategic options that should be considered for strategy formulation? - Evolving supply chain management: internet of things - Santos, Tomás Duarte Rosa (2022)
This project focus on the analysis of the organized food retail industry in Portugal, up to 2030. For this purpose, four scenarios were created using two critical uncertainties-shoppers’ e-commerce usage and producers’ direct-to-consumer adoption-and recommendations were developed. Moreover, the applications and impact that Internet of Things can have in supply chain management were considered for analysis, as this technology is evolving and already disrupting the way the supply chain operates. It is concluded that the key break throughs are on processes optimization, control of operations, communication across the whole supply chain and the information extracted throughout the full process.